Base Excitation Vibration Isolation Utilizing Magnetorheological Elastomer Models: A Simulation Study (ELEKTRIKA- Journal of Electrical Engineering, 2021)
Smart materials are those whose characteristics can be changed by external stimuli like temperature, pressure, and magnetic fields. Magnetorheological Elastomer (MRE) is a smart composite material made up of a polymer matrix with ferromagnetic particles incorporated in it. The interaction between the magnetic particles in an external magnetic field changes its mechanical characteristics, such as stiffness. The purpose of this article is to study the characteristics of several MRE models on a base motion isolation system. The loops of several MRE models from the literature, such as Bingham, Bouc-Wen, Modified Bouc-Wen, Dahl, and Hysteresis models, were simulated using SIMULINK and MATLAB on a base motion isolation (base excitation) system in this study. This is achieved by obtaining the time-domain results, and a 2nd order underdamped system analysis is used to study the behaviour and characteristics of the MREs. All these models are simulated, and their displacements with respect to time plots are obtained. The input signals that excite the base are a step and sinusoidal wave. Mathematical expressions identified Field-dependent parameters for each model are used form the literature. Results were analysed using the 2nd order underdamped system characteristics such as %PO, Tr and Ts. All of those parameters decreased when the applied current increases. Time-domain results reveal that as the current is increased, the damping is lightened and the stiffness is increased, due to the MRE's field-stiffening characteristics under a magnet field.